2016
DOI: 10.1016/j.ejpb.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer activity of doxorubicin-loaded liposomes co-modified with transferrin and folic acid

Abstract: Cancer-specific drug delivery represents an attractive approach to prevent undesirable side-effects and increase the accumulation of the drug in the tumor. Surface modification of nanoparticles such as liposomes with targeting moieties specific to the up-regulated receptors on the surface of tumor cells thus represents an effective strategy. Furthermore, since this receptor expression can be heterogeneous, using a dual-combination of targeting moieties may prove advantageous. With this in mind, the anti-cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 46 publications
5
44
0
1
Order By: Relevance
“…Nanoparticles, decorated with Pep‐1 and CGKRK, were observed to enhance the delivery of paclitaxel into MCTS compared to nanoparticles with only one ligand . Similar observations were made by combining folic acid and transferrin as two targeting ligands on a liposome showing a significant increase in HeLa spheroid association compared to nanoparticles with single targeting ligands …”
Section: Using Mcts To Evaluate Nano Drug Carrierssupporting
confidence: 61%
“…Nanoparticles, decorated with Pep‐1 and CGKRK, were observed to enhance the delivery of paclitaxel into MCTS compared to nanoparticles with only one ligand . Similar observations were made by combining folic acid and transferrin as two targeting ligands on a liposome showing a significant increase in HeLa spheroid association compared to nanoparticles with single targeting ligands …”
Section: Using Mcts To Evaluate Nano Drug Carrierssupporting
confidence: 61%
“…DOX can inhibit the replication of tumor cells by intercalating in the base pairs of DNA 9. Also, it induces apoptosis in cancerous cells as a result of oxidative damage to DNA 11. However, despite the fact that it is a very potent chemotherapeutic agent, its clinical use is limited by its induced toxicity and drug resistance 8.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that stealth liposomes are efficient carriers for drugs, genes, and vaccines and can be easily tailored with proteins, antibodies, and other suitable ligands, resulting in smart formulations for targeted drug delivery [47]. Furthermore, liposomes conjugated with folic acid and transferrin showed higher cell association, penetration, and efficacy of delivering doxorubicin in vitro in human cervical carcinoma cell line (HeLa) as compared with either of the single-ligand targeted liposomes, or non-targeted liposomes [48]. …”
Section: Systemic Versus Localized Drug Delivery Systemsmentioning
confidence: 99%
“…No.Drug/antibodyType/composition of liposomesCell lines/animal/clinical modelsReference1.PaclitaxelStearyl amine-based positively charged multilayered liposomesHeLa cell lines[42]2.CisplatinME-180 cervical cancer cell line, cisplatin-resistant clone R-ME-180 and HeLa cells[43]3.CisplatinHeat-activated thermosensitive liposome[44]4.DoxorubicinCervical cancer patients[45]5.IL-2Anionic, cationic, and neutral liposomesINBL cells 6.DoxorubicinTransferrin (Tf)-conjugated stealth liposomes (Tf-SL-DOX)[47]7.DoxorubicinLiposomes conjugated with folic acid and transferrinHeLa cells[48]8.IL-2Cationic liposome containingINBL cells induced tumor-containing immune-depressed CBA mice[49] …”
Section: Systemic Versus Localized Drug Delivery Systemsmentioning
confidence: 99%